Raízes de Portugal: do Minho a São Paulo (1950-2000) - Matos, Talita Carneiro de (2016)
The search for "Roots of Portugal. From Minho to São Paulo (1950-2000)" aims to understand and discuss the participation of Portuguese, their descendants and people of other nationalities, groups and associations considered by its members as representatives of the" folklore "Portuguese in Sao Paulo. It discusses the origin of its popular representation and his ways by other continents, focusing on the city of São Paulo and associations as aggregator. The study was conducted through oral history and other sources, who conversed with the tradition of studies, popular culture, memory, ruptures and continuities of a representation that is focused on reinventions of these traditions, seeking to revive the concept of crystallization that the word folklore emanates. Practice looking reinserting a local culture, representative of a country for the Portuguese immigrants who willingly or by political and economic pressures, reunited and/or were recognized as members of this community through associations